Extracting Meaning: Toward a restored collective memory - Roets, Chamonix (School of Architecture, Planning and Geomatics, 2023)
Spaces hold memories, both good and bad. Preserved in the landscapes of the City of Cape Town is many unspoken memories of past events. Higgovale Quarry is one of these. This void was laboured to supply the stone that built the Rhodes memorial, among many other buildings that created this colonial city of the 1800s. The problem is twofold. Firstly, the people most affected by Rhodes's actions, the marginalised people of Cape town do not have access to Table Mountain, the symbol of the city. Secondly, there is a need to rethink the way memorials are made and memories are captured. The days of employing traditional memorials to capture collective memories are numbered. There is an opportunity to challenge the linearity and one-sidedness of traditional static memorials and discover means to dynamic ways of memorialising that aim to engage the everyday experience interactively. The aim is to mobilise the Higgovale quarry as a site of active consciousness that can contribute to the restoration of collective memory and access to the mountain. Therefore, I am designing a cultural centre. I am doing this by creating an intervention that can display dynamically the memories of the space through the design, as well as be a stage for the memories to be displayed through performance by people from diverse cultures. I aim to sculpt a space that memorialises by framing memories dynamically through the abstract, interactive building as a memorial.